Print Culture and the Blackwood Tradition. - Finkelstein, David (Studies in book and print culture., 2006)
Two hundred years after the founding of this significant influence on British literary, political, and social history, this collection of essays reappraises the place of the Blackwood firm and its magazine in literary and print culture history.